Illness Perceptions, Medication Beliefs, and Adherence to Antiretrovirals and Medications for Comorbidities in Adults With HIV Infection and Hypertension or Chronic Kidney Disease. (1st December 2016) - Weiss, Jeffrey J.; Konstantinidis, Ioannis; Boueilh, Anna; Fierer, Daniel S.; Gardenier, Donald; Barber, Mark G.; Kang, Tony; Kress, Anna; Ericson, Katherine; Lira, Marlene C.; Yostos, Marina P.; Bogner, Hillary R.; et al.
Abstract : Background: Mortality in patients with HIV infection is increasingly due to comorbid medical conditions. Research on how adherence to medications for comorbidities relates to antiretroviral (ARV) medication adherence and how interrelations between illness perceptions and medication beliefs about HIV and comorbidities affect medication adherence is needed to inform adherence interventions. Methods: HIV-infected adults with hypertension (HTN) (n = 151) or chronic kidney disease (CKD; n = 41) were recruited from ambulatory practices at an academic medical center. Illness perceptions and medication beliefs about HIV and HTN or CKD were assessed and adherence to one ARV medication and one medication for either HTN or CKD was electronically monitored for 10 weeks. Results: Rates of taking, dosing, and timing adherence to ARV medication did not differ from adherence to medication for HTN or CKD, with the exception that patients were more adherent to the timing of their ARV (78%) than to the timing of their antihypertensive (68%; P = 0.01). Patients viewed HIV as better understood, more chronic, having more negative consequences, and eliciting more emotions, compared with HTN. Patients viewed ARVs as more necessary than medication for HTN or CKD. Having a realistic view of the efficacy of ARVs (r = −0.20; P < 0.05) and a high level of perceived HIV understanding (r = 0.21; P < 0.05) correlated with better ARV adherence. Conclusions: Patients with HIV showed similar rates of adherence to ARVs as to medications for comorbidities, despite perceiving HIV as more threatening and ARVs as more important. This can be used in adapting existing interventions for ARV adherence to encompass adherence to medications for comorbid conditions. Abstract : Supplemental Digital Content is Available in the Text.